Reversals of fortune: Shared governance, “democracy,” and reiterated problem-solving - Thurston, T. L. (Frontiers in Political Science, 2022)
What can the deep past tell us about how 'good government' is instituted, replicated and maintained through time? After a comparative look at late prehistoric political formation in Western Eurasia, especially the far west today called Europe, a case study from Sweden is examined. During the Iron Age, systems of participatory governance developed across Europe, perhaps in response to autocracies of the previous Bronze Age. Heterarchic structures with systems of checks and balances provided voice for ordinary people as well as leaders, but there were clear 'reversals of fortune', as autocracy and more egalitarian structures were interspersed through time. The cycle in much of Europe was interrupted by Roman and later continental empires, but a case study from Sweden, with its less disrupted history, illustrates indigenous political cycles from the prehistoric Iron Age to medieval times (500 BCE-1550 CE). Historians typically frame this record as series of unrelated 'ages' divided into standard time periods defined by specific struggles. Here, I argue that the record is better interpreted as one long, shifting sequence, during which common people maintained a strong social memory and defended their rights - aware of their political past, planning for their political future, and sometimes erupting into political violence. In connection with this prehistoric into historic trajectory, a number of current theories and mixed methods from anthropological archaeology, theoretical political science and theoretical sociology are reviewed, dealing with regime change, democratic movements, diffusion, and waves, contingency theories, reiterated problem solving and event structure analysis. The so-called 'Long Iron Age' is consequently seen as an extended period of tension between different forms of government, different political ideologies, and the dynamic negotiation of sociopolitical norms, with repercussions that extend into recent times.